Reciprocity in young children - Sandra Dahlman; Pontus Ljungqvist; Magnus Johannesson (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
Reciprocal behavior, the rewarding of kind acts and the punishment of unkind acts, is relatively well established among adults. We test if reciprocal behavior exists already among children 3-8 years old. Three simple anonymous allocation games are conducted with 242 children. In a first stage, half of the children decide whether to give a bag of raisin to another anonymous child or not. The three games differ in terms of the cost of giving and the relative difference in payoffs. In a second stage the roles are reversed between the two children to test for reciprocal behavior. We find reciprocal behavior in all three games with highly significant effects for two of the three games. Furthermore, the degree of reciprocity tends to increase with age. The effect of reciprocity is not significant among 3-5 year old children, whereas the effect is highly significant in all three games for 6-8 year olds.
Keywords: C90; D64; J13; 330; Reciprocity; prosociality; children; experiments; Kinder; Soziale Beziehungen; Test; Verhalten; Schweden